1997
DOI: 10.1097/00005131-199708000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging for Irreducible Posterolateral Knee Dislocation

Abstract: Magnetic resonance imaging (MRI) of an irreducible knee dislocation can help physicians evaluate associated bone and ligamentous lesions. However, caution should be taken when interpreting the images because the capsuloligamentous interposition seen in irreducible knee dislocations may be misdiagnosed as a meniscal lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A review of several recent cases, clearly defined as posterolateral dislocations, revealed only 1 case of accompanying neurologic injury. 3,8,12,13 Neurologic deficits are infrequent, but peroneal nerve injury is more common among posterolateral types than other dislocations. 9 Vascular injury from a rotary mechanism occurs less frequently compared to other types of dislocation.…”
Section: Mri Findings In Our Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A review of several recent cases, clearly defined as posterolateral dislocations, revealed only 1 case of accompanying neurologic injury. 3,8,12,13 Neurologic deficits are infrequent, but peroneal nerve injury is more common among posterolateral types than other dislocations. 9 Vascular injury from a rotary mechanism occurs less frequently compared to other types of dislocation.…”
Section: Mri Findings In Our Studymentioning
confidence: 99%
“…The associated findings in previous reports include lateral patellar subluxation, 12 inferior descent of the patella, 12 cruciate ligament tears, 3,4,6,10,12,13 impaction fracture of the posterior margin of the lateral tibia plateau, 12 avulsion of the posterior horn of the medial and lateral menisci, 8 and quadriceps tendon rupture. 3 No mention of the posterolateral structures was made in any previous reports.…”
mentioning
confidence: 92%
“…Entrapment of the capsuloligamentary elements in the intercondylar notch, with or without dislocation of the patella, is the specific causal mechanism for irreducible dislocation [7][8][9] . Up until now, incarcerated patellar tendon 10 , vastus medialis [11][12][13][14] , anteromedial capsule and retinaculum 3 , and the major part-the medial capsuloligamentary structures such as the medial capsule, the medial retinacular structures and the medial collateral ligament [1][2][3][4]6,8,11,[15][16][17][18][19][20] , have been emphasized as the principle factors which prevent closed manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Irreducible knee dislocation usually results from posterolateral dislocation but may exceptionally occur after lateral dislocation 19 . The medial collateral ligament and both cruciate ligaments are often injured in irreducible knee dislocations, but the lateral ligaments are usually spared 2,6,21 .…”
Section: W Chen Et Al Irreducible Lateral Knee Dislocationmentioning
confidence: 99%
See 1 more Smart Citation